Dietary Diversity and Nutritional Status of School Children in Pyin Oo Lwin township, Mandalay Region, Myanmar - Zaw, PannEi; soe, Lethandar (Journal of Global Nutrition, 2024)
The nutritional status of school children is important for their growth, development, and overall well-being. Poor nutritional status of the school children can have a huge impact not only in the short term but also for their long lives. This study aimed to investigate the nutritional status and its associated factors among adolescent school children in Pyin Oo Lwin Township, Mandalay Region. A cross-sectional study was conducted from August to December 2023 among 202 school children in public schools of Pyin Oo Lwin Township by simple random sampling method using face-to-face interviews with pretested structured questionnaires. Anthropometric measures were taken, and nutritional indicators were calculated using the WHO Anthro Plus software. Data analysis was conducted using SPSS version 16. Bivariate and multivariable regression analyses were performed to find the associated factors of nutritional status. Among 202 students, aged between 14 and 18 years, 83.7% had normal nutritional status while the prevalence of thinness, overweight, and obesity were 12.4%, 3%, and 1%. Most of the school adolescents had a high knowledge level (80.7%), and 77.2% had adequate dietary diversity. According to multivariable analysis, dietary diversity was the major influencing factor on malnutrition of the school children. The students with an adequate dietary diversity score were 70% less likely to be malnourished compared to those with an inadequate diversity score [AOR= 0.30, 95%CI = (0.13, 0.67), p-value=0.003]. Therefore, the study would like to recommend promoting nutrition education specifically on diverse food consumption to achieve a balanced diet and prevent malnutrition among the students.